Burnout before and during COVID: A systematic review and meta‐analysis of 48 698 trainees. - Prentice, Shaun; Dorstyn, Diana S.; Massy‐Westropp, Nicola; Benson, Jill; Elliott, Taryn (Medical Education, 2025)
Purpose: Postgraduate medical trainees exhibit elevated burnout levels. COVID‐related workplace stressors created a further mental health challenge, potentially exacerbating this issue. This review compared literature on burnout levels in postgraduate medical trainees published before and after COVID, with consideration of group differences (e.g., specialty and country). Methods: This systematic review and meta‐analysis was registered on PROSPERO (CRD42023404618) and followed the updated PRISMA statement. Embase, Ovid Medline, Ovid PsycInfo and the Cochrane Collaborative were searched until April 2025. These results were supplemented with pearling and citation searching of included articles and previous reviews. Studies that administered the Maslach Burnout Inventory – Human Services Survey (MBI) to postgraduate medical trainees were eligible. Where studies met eligibility criteria but did not provide required data (i.e., sample size, means and standard deviations), authors were contacted to supply these data. Methodological reporting quality (QualSyst tool) and publication bias were assessed (funnel plots, trim‐and‐fill method), and between‐group heterogeneity explored (subgroup analyses, meta‐regression). Differences in burnout levels pre‐ and intra‐COVID (i.e., before and after March 2020, respectively) were quantified using Hedges' g. Results: Of 3 930 unique studies identified, 245 were included, comprising 48 698 trainees. Impacts of the COVID‐19 pandemic on burnout levels varied: although trainees' emotional exhaustion remained stable, reported levels of depersonalisation (from gw = 0.611 to 0.430, p = 0.045) and personal accomplishment fell (from gw = −0.348 to −0.626, p = 0.009). Specialty and country variations were evident, with emergency medicine trainees trainees reporting worse burnout during COVID, whereas anethesiology, psychiatry and urology trainees felt less burnt out by their work. Conclusions: Wellbeing supports should be prioritized for front‐line specialty trainees, who were vulnerable to work‐related stressors that emerged during COVID. Interventions should focus on fostering a sense of competence and mastery, both of which can enhance personal accomplishment. Through meta‐analysis of 48,698 interns and residents, Prentice et al. report that lowered personal accomplishment during the COVID‐19 pandemic was associated with practice specialty.